Improved 3D limit-cycle navigation method for path planning quad rotor - Akbar, Fajril; Mohd Mustafah, Yasir (IOP Publishing, 2013)
Quad rotors as a type of rotary wing aerial vehicle must planned their flight path effectively and avoid any disturbance to complete their mission. The extension of 2D limit-cycle navigation into 3D, made it possible to apply for aerial vehicle. The extended limit-cycle has been introduced, but it generate unsuitable path in certain condition. In this research, rendering the obstacle into a cylinder will generate the efficient path and provide the best way in avoiding stationary obstacle. By defining obstacle position, a simulation and performance study is done using limit-cycle characteristic method. The simulations results illustrated the path generation using improved 3D limit cycle with different obstacle condition.